Detection of Mycobacterial Lipoarabinomannan with A Monoclonal Antibody Qualitative ELISA in Urine of Tuberculous Meningitis Patients - Sylvia Rachmayati; Anita Liliana Susanti; Basti Andriyoko (The Indonesian Biomedical Journal, 2016)
BACKGROUND: Tuberculous meningitis is the most severe manifestation of tuberculosis. The diagnostic approach of tuberculous meningitis is difficult. Combination of clinical, laboratory and radiological criteria were used in diagnostic approach of tuberculous meningitis. Urinary mycobacterial lipoarabinomannan (LAM) antigen detection is a promising diagnostic tool. Detection of mycobacterial antigen in concentrated urine sample is predicted to improve the positivity rate of the qualitative enzyme-linked immunosorbent assay (ELISA) diagnostic tool. The purpose of this study is to examine the detection ability of a monoclonal antibody qualitative ELISA in concentrated and unconcentrated urine of tuberculous meningitis patients.METHODS: This research is a descriptive, crosssectionally designed. The study was conducted in the Clinical Pathology Department laboratory of Dr. Hasan Sadikin Hospital, in July-October 2014. A total of 27 patients diagnosed as tuberculous meningitis patients were included and the subjects were classified into possible and probable criteria according to consensus criteria. The subjects were classified as definite if the cerebrospinal fluid culture was positive for Mycobacterial tuberculosis growth. The subjects were examined for the presence of LAM in unconcentrated and concentrated urine with a monoclonal antibody qualitative ELISA method.RESULTS: Unconcentrated urinary LAM examination positivity was 0% while in concentrated urine was 14.8%. The positivity of concentrated urinary LAM were higher among the definite criteria group.CONCLUSION: Concentrating urine sample increase the positivity rate of urinary LAM detection with ELISA method as high as 14.8%. The urinary antigen detection is higher among the definite tuberculous meningitis patients.KEYWORDS: LAM, concentrated urine, tuberculous meningitis, qualitative ELISA